Pengaruh Modal, Tenaga Kerja dan Bahan Baku terhadap Pendapatan Industri Kain Sasirangan ( Studi Pada Kampung Sasirangan Seberang Mesjid ) - Maulida, Eka Nor; Pahlevi, Khairi (PPJP ULM, 2024)
This study examines the low income of entrepreneurs in the Sasirangan fabric industry in Sasirangan Village, Banjarmasin, South Kalimantan. Although Sasirangan cloth has high aesthetic value and stable demand, especially as a mandatory uniform in South Kalimantan, the craftsmen receive very low wages. This study aims to analyze the effect of capital, labor, and raw materials on the income of Kain Sasirangan entrepreneurs, in order to provide a better understanding and solutions to improve the welfare of craftsmen and the sustainability of this industryThis research was conducted in JI Seberang Mesjid, Central Banjarmasin District, Banjarmasin City, South Kalimantan Province. Using SPSS 25 program for multiple Linear regression analysis. According to the findings of this study, capital, labor, and raw materials have a major effect on the income of the Sasirangan Industry in Banjarmasin City. Capital has a favorable and considerable influence on the income of the Sasirangan Industry in Banjarmasin City. Labor has a negative and small effect on the income of the Sasirangan Industry in Banjarmasin City. Raw materials have a favorable but negligible impact on the income of the Sasirangan Industry in Banjarmasin City.